Complainers' resource investment and mobilization in digital environments using Conservation of Resources theory - Beh, Yean Shan; Sajtos, Laszlo; Cao, Joanne T (International journal of service industry management, 2020)
PurposeThe purpose of this paper is to consider whether consumers can recover from a service failure by utilizing internal and external energy resources that are available to them at the time of an online complaint. Based on the Conservation of Resources (COR) theory, this research conceptualizes the complainers' act of complaining through internal and external energy resources. By investing (direct utilization of resources) and mobilizing (utilizing resources to change the trajectory of a loss) these resources, this study aims to understand which resources (internal or external) and what strategies (investment or mobilization) are effective in the face of a resource loss.Design//methodology/approachStudy 1 aimed to test the impact of energy resources (motivation and affordance) on consumers' negative emotions and satisfaction with their complaints through an online panel survey. Study 2 was a between-subjects design experiment aimed to overcome the diversity of the circumstances around a service failure, complaint motivation and complaints that were captured in Study 1.FindingsThis study provides evidence of the negative and positive effects of internal and external energy resources, respectively, in altering the consumer's emotions and behavioral intentions. The findings of this study underline the role of affordances of features, specifically perceived conversationality of digital features, in improving consumers' relationship with the defaulting firm.Practical implicationsBased on the findings related to the perceived conversationality of digital features, managers are urged to explore the affordances of online features that consumers use for communications, in general, or for complaints, in particular.Originality/valueTo our understanding, this paper is the first study to employ COR theory as a conceptual background, and in turn, the first to conceptualize complaint motivations and online complaint features as internal and external resources, respectively. As such, this study is the first of its kind to examine complaint media systematically.